2019
DOI: 10.1109/jqe.2019.2909191
|View full text |Cite
|
Sign up to set email alerts
|

Chaos Bandwidth Enhancement of Fabry–Pérot Laser Diode With Dual-Mode Continuous-Wave Optical Injection

Abstract: We show numerically that dual-mode continueswave optical injection into a Fabry-Pérot laser diode subject to optical feedback generates a chaos bandwidth which is four to six times that without optical injection. As a comparison, it is shown that single-mode optical injection can increase the chaos bandwidth threefold with careful choice of detuning. Any combination of dual-mode injection will further enhance the chaos bandwidth and especially for strong injection and over relatively large positive detuning ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The corresponding theoretical research showed that this method can be used to achieve a high bandwidth chaotic signal in a wider range of parameters in 2019. 55 Jiang et al used an external-cavity semiconductor laser (ECSL) to obtain a broadband chaotic signal from the selfphase modulated optical injection structure experimentally in 2020. 57 The experimental setup is shown in Figure 2 (B1).…”
Section: Unidirectional Optical Injection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding theoretical research showed that this method can be used to achieve a high bandwidth chaotic signal in a wider range of parameters in 2019. 55 Jiang et al used an external-cavity semiconductor laser (ECSL) to obtain a broadband chaotic signal from the selfphase modulated optical injection structure experimentally in 2020. 57 The experimental setup is shown in Figure 2 (B1).…”
Section: Unidirectional Optical Injection Methodsmentioning
confidence: 99%
“…44 The flatness refers to the range of spectrum fluctuation within the bandwidth. In order to eliminate the influence of relaxation oscillation frequency on the bandwidth and flatness of chaotic laser, researchers have carried out extensive studies, including improved optical feedback, [45][46][47][48][49][50] unidirectional optical injection, [51][52][53][54][55][56][57][58][59] mutual injection, 60,61 and subsequent processing 62,63 of chaotic laser.…”
Section: Bandwidth Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on expanding Lang-Kobayashi equations [24], an FP laser subjected to optical feedback can be described as [25,26]:…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The higher dimensional computation for the emerging artificial intelligence can be realized due to RC with the simple hardware structure and the short-time training algorithm. Compared with the approach of realizing artificial neural networks on a personal computer by a software, the RC can be implemented by hardware and can improve the performance of traditional artificial neural networks [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%